Study of polishing using abrasive belts on compliant contact wheels in normal and sliding contact - Chow, Timothy E-Liang (2017)
Many manufacturing lines employ the use of robotic technology to speed up processes and also provide a more efficient and consistent end result. However, polishing and grinding surfaces with the need of high accuracy and precision especially in the aerospace industry are mostly done manually due the complexity of various precision components such as turbine and impeller blades. These components place huge importance in surface roughness as well as peak to valley values to reduce as much drag as possible. While much research has been done on the pressure distribution on compliant surfaces, there is not much work has been done to evaluate the effects of compliance on the distribution of forces in the contact area of the tool and work pieces in both normal and sliding contact. In this project, pressure distribution was predicted and modelled with Hertzian’s Theory of Contact and was compared to the data collected from the pressure film sensors. The work piece is then subjected to different parameters under robotic polishing to determine the surface roughness and material removal volume. This project experiment is focused on two feed rates (0 and 5mm/s) and both flat and convex work piece surfaces. Further investigations using other feed rates and other complex surfaces will further improve this study to predict the surface profile and material volume in compliant coated abrasive tool polishing.